Uncovering Anti-Inflammatory Activity of Ginsenoside Rg1 in a Wound-Inured Zebrafish Model by GC-MS-based Chemical Profiling - Hsu, Su-Jung; He, Min; Salomé-Abarca, Luis Francisco; Choi, Young Hae; Wang, Mei (Planta Medica, 2025)
There is growing evidence highlighting the pivotal role of cellular metabolic adaptation in governing diverse immune responses, as well as the capacity of immune cells to alter metabolic preferences. In both scenarios, the prospect of leveraging bioactive compounds to induce metabolic reprogramming emerges as a novel adjuvant strategy for clinical immunotherapy. Rg1, a major active ginsenoside found in ginseng roots, has the potential to function as a glucocorticoid receptor agonist. Unraveling the intricate relationship between anti-inflammatory functions and the metabolic effects of ginsenosides and glucocorticoids may contribute to the identification of metabolic biomarkers associated with anti-inflammation. This research aims to determine endogenous metabolic response differences evoked by Rg1 and glucocorticoids underlying in vivo anti-inflammatory responses. The metabolic impact, particularly on primary metabolites, was assessed in zebrafish embryos using gas chromatography–mass spectrometry (GC-MS) in conjunction with metabolic pathways analysis via the KEGG pathway database. Our results indicated that Rg1 possesses a similar effect in alleviating inflammation in treating injured zebrafish as beclomethasone. The anti-inflammatory effects of Rg1 are achieved by inhibiting the neutrophils and macrophages toward the amputated edges and upregulating gene expression associated with pro-inflammatory cytokines. The anti-inflammatory effects of Rg1 also include changes in fatty-acid metabolism and downstream aromatic amino acids in the TCA cycle. Therefore, Rg1 may be a promising drug candidate for treating inflammatory responses and a valuable supplement for enhancing immune regulation.
Keywords: Panax ginseng; ginsenosides Rg1; metabolomics; gas chromatography/mass spectrometry; wound-injured inflammation; zebrafish